The Species Identification and Genomic Analysis of Haemobacillus shengwangii: A Novel Pathogenic Bacterium Isolated From a Critically Ill Patient With Bloodstream Infection - Du, Yingying; Li, Xuming; Liu, Yuhao; Mu, Shikui; Shen, Dandan; Fan, Shu; Lou, Zheng; Zhang, Shouqin; Xia, Han; Yuan, Yinghua; Wang, Sheng (Frontiers in Microbiology, 2022)
Since the first strain related to Thermicanaceae was reported in 1999, almost no literature on Thermicanaceae is available, particularly its genomics. We recently isolated a novel pathogenic bacterium, the △ strain DYY3, from the blood sample of a critically ill patient. The morphological, physiological, and biochemical characteristics of △ strain DYY3 were presented in this study, and the virulence factor genes and antibiotic resistance of DYY3 were also determined. Interestingly, the average nucleotide identity (ANI) and core-genes average amino acid identity (cAAI) analysis indicated that △ strain DYY3 was genus novel and species novel. Moreover, phylogenetic analysis based on both 16S rRNA gene and whole genomic core gene sequences suggested that △ strain DYY3 belonged to the family Thermicanaceae, and this novel taxon was thus named Haemobacillus shengwangii gen. nov., sp. nov. Besides, both the whole genome-based phylogenetic tree and amino acid identity analysis indicated that Thermicanus aegyptius, Hydrogenibacillus schlegelii, Brockia lithotrophica, and the newly discovered species H. shengwangii should belong to Thermicanaceae at the family level, and T. aegyptius was the closest species to H. shengwangii. We also constructed the first high-quality genome in the family Thermicanaceae using the next-generation sequencing (NGS) and single-molecule real-time (SMRT) sequencing technologies, which certainly contributed to further genomics studies and metagenomic-based pathogenic detection in the future.